A Study of the Emergence and Spread of the Plague Epidemic in Egypt from the Old Kingdom to the End of the Roman Era - Amor, BOUSBIA; Fatiha, GHEDIRI (Journal of Posthumanism, 2024)
This study examines the spread of the plague epidemic in Egypt during the Old Kingdom, based on literary sources, which describe the methods adopted by the Egyptians to combat this disease, including the existence of physicians specializing in specific parts of the body, alongside others who focused on seasonal diseases that were not clearly identified, among which the plague is presumed to have been included. Both Herodotus and the Jewish historian Josephus, as well as accounts found in the sacred texts, referred to this epidemic, which affected Egypt, Jerusalem, and parts of North Africa during the Roman period. In terms of archaeological evidence, reports by specialized scientific missions have revealed skeletal remains and ceramic materials associated with a system for the cremation of infected corpses, thus completing the picture of this devastating epidemic, which repeatedly affected the Egyptian kingdom and other regions of the ancient world. Nonetheless, it is noteworthy that the Egyptians managed such epidemics through a healthcare system that allowed them to minimize substantial loss of life.